2019
DOI: 10.1080/01635581.2018.1559938
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Circulating Levels of 25-hydroxyvitamin D3 in Breast Cancer Patients Receiving Chemotherapy

Abstract: Cancer treatments, toxicities and their effects on lifestyle, may impact levels of vitamin D. The aim of this study was to determine serum 25-hydroxyvitamin D3 (25(OH)D 3) levels before, directly after and 6 months after chemotherapy in breast cancer patients (n ¼ 95), and a comparison group of women (n ¼ 52) not diagnosed with cancer. Changes in 25(OH)D 3 levels over time were compared using linear mixed models adjusted for age and season of blood sampling. Before start of chemotherapy, 25(OH)D 3 levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…In our study, the blood collection was performed at the time of diagnosis which allowed us to avoid any confounding effects due to BC treatment. As previously reported, BC therapy can alter plasma vitamin D levels [47,48]. It has been reported that after 6 months of chemotherapy, vitamin D levels can be reduced to almost 5.52 ng/mL (p = 0.003).…”
Section: Discussionmentioning
confidence: 55%
“…In our study, the blood collection was performed at the time of diagnosis which allowed us to avoid any confounding effects due to BC treatment. As previously reported, BC therapy can alter plasma vitamin D levels [47,48]. It has been reported that after 6 months of chemotherapy, vitamin D levels can be reduced to almost 5.52 ng/mL (p = 0.003).…”
Section: Discussionmentioning
confidence: 55%
“…This value is even lower than the percentage of patients with VD insufficiency on D1C6, although only 36% of patients were still taking VD supplementation at month 24 of follow-up. This could be partly explained by previous studies showing a decrease in 25-OH VD concentration during chemotherapy and a recovery after treatment end [27][28][29]. It has been suggested that taxanes, corticosteroids, behavioral changes (such as sunlight exposure, dietary intake), and gastrointestinal side-effects play a role in this initial decrease in 25-OH VD levels [27][28][29][30].…”
Section: Discussionmentioning
confidence: 93%
“…This could be partly explained by previous studies showing a decrease in 25-OH VD concentration during chemotherapy and a recovery after treatment end [27][28][29]. It has been suggested that taxanes, corticosteroids, behavioral changes (such as sunlight exposure, dietary intake), and gastrointestinal side-effects play a role in this initial decrease in 25-OH VD levels [27][28][29][30]. This could explain the important 25-OH VD concentration decrease at month 12 of follow-up (only 28.9% of patients with normalized 25-OH VD level).…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, all patients received blood sampling at the time of diagnosis and prior to the start of treatment. In particular, patients with aggressive (e.g., triple negative carcinomas) or advanced tumor stages (cT3/4, cN+) were treated with (neo-) adjuvant chemotherapy, and it is well known that chemotherapy can lead to decreased 25(OH)D levels [ 50 , 51 , 52 ]. In the cited studies [ 48 , 49 ], the time of 25(OH)D level determination was very heterogenous.…”
Section: Discussionmentioning
confidence: 99%